2022
DOI: 10.3390/biom12121737
|View full text |Cite
|
Sign up to set email alerts
|

Protective Actions in Apical Periodontitis: The Regenerative Bioactivities Led by Mesenchymal Stem Cells

Abstract: Resulting from bacterial infection, apical periodontitis (AP) is a common inflammatory disease of the periapical region of the tooth. The regeneration of the destroyed periapical alveolar bone and the surrounding periodontium tissues has long been a difficult task in clinical practice. These lesions are closely related to pathogen invasion and an overreactive immune response. It is worth noting that the protective healing process occurs simultaneously, in which mesenchymal stem cells (MSCs) have a crucial func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Bone destruction is a major pathological factor in chronic inflammatory diseases such as AP. Various cytokines including TNF-α, IL-1α, and IL-6 were released by immunocytes to recruit the osteoclast precursors and induce the maturation of osteoclasts ( Lyu et al, 2022 ). We have detected osteoclast markers including Ctsk , Acp5 , Mmp9 , and Nfatc1 by scRNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…Bone destruction is a major pathological factor in chronic inflammatory diseases such as AP. Various cytokines including TNF-α, IL-1α, and IL-6 were released by immunocytes to recruit the osteoclast precursors and induce the maturation of osteoclasts ( Lyu et al, 2022 ). We have detected osteoclast markers including Ctsk , Acp5 , Mmp9 , and Nfatc1 by scRNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with previous studies using different cultivable or noncultivable methods. [20–22] However, Firmicutes , Proteobacteria , Actinobacteria , and Bacteroidetes were found to be prevalent in chronic apical periodontitis cases. [23,24] More specifically, the members of the genera Streptococcus , Lactobacillus , and Prevotella were highly associated with acute apical periodontitis intracanal samples.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been reported that SCAPs may have superior osteogenic differentiation capacity compared to bone marrow mesenchymal stem cells (BMSCs) ( 10 ). Nonetheless, it was also reported that an inflammatory microenvironment could alter the hallmarks of SCAPs, leading to an inhibitory or increasing effect on osteogenic differentiation ( 11 , 12 ). Effective osteogenic differentiation of MSCs is regulated by numerous factors, including physical, chemical, and biological factors, which may stimulate different signaling pathways, transcription factors, and microRNAs (miRNAs), to direct MSCs differentiated toward osteoblast lineage ( 13 16 ).…”
Section: Introductionmentioning
confidence: 99%